2022
DOI: 10.3389/fgene.2022.1000460
|View full text |Cite
|
Sign up to set email alerts
|

Gene set-based identification of two immune subtypes of diffuse large B cell lymphoma for guiding immune checkpoint blocking therapy

Abstract: Background: Diffuse large B cell lymphoma (DLBCL) is the most common lymphoma in adults. Tumour microenvironment is closely related to tumour prognosis and immune checkpoint blocking therapy (ICBT). This study aimed to investigate the immunological and prognostic characteristics of the tumour microenvironment (TME), as well as the regulatory mechanisms.Methods: Gene expression profiles and clinical data of patients with DLBCL were obtained from GEO database. ESTIMATE, CIBERSORT, and ssGSEA analyses were used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 77 publications
(69 reference statements)
0
0
0
Order By: Relevance
“…Interestingly, previous studies conducted in 2015 also reported reduced expression of CD247 in NK/T-cell lymphoma [19]. The subsequent discovery made by scholars unveiled a signi cant association between the high expression of CD247 in DLBCL and enhanced overall survival [20]. Our studies consistently support the aforementioned perspective.…”
Section: Discussionsupporting
confidence: 88%
“…Interestingly, previous studies conducted in 2015 also reported reduced expression of CD247 in NK/T-cell lymphoma [19]. The subsequent discovery made by scholars unveiled a signi cant association between the high expression of CD247 in DLBCL and enhanced overall survival [20]. Our studies consistently support the aforementioned perspective.…”
Section: Discussionsupporting
confidence: 88%